Synthetic Studies towards NG-121: Diastereoselective Synthesis of NG-121 Methyl Ether - Singh, Mandeep; Argade, Narshinha P. (Synthesis, 2012)
Starting from unsymmetrically O-protected methyl 4-bromo-3,5-dihydroxybenzoate, a facile synthesis of the methyl ether of bioactive natural product NG-121 was accomplished in very good overall yield. The key steps were: Stille coupling reaction of the farnesyl unit with the electron-rich phenolic segment; hydroxy-directed selective epoxidation of the farnesyl chain along with concomitant phenol-driven intramolecular regio- and diastereoselective ring closure to the corresponding hydroxybenzopyran; and regioselective formylation followed by in situ reductive lactonization.
Keywords: 4-bromo-3,5-dihydroxybenzoate; Stille coupling; intramolecular cyclization; formylation; lactonization; NG-121 methyl ether